2021
DOI: 10.1080/09286586.2021.1875012
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Trauma During the COVID-19 Lockdown

Abstract: Purpose: To identify the impact the COVID-19 lockdown had on the presentation and management of sight-threatening ocular trauma. Methods: A retrospective cohort analysis of all patients who presented to the Ophthalmology department of Royal Hallamshire Hospital Sheffield with serious ocular trauma during the COVID-19 lockdown period was performed. Data on mechanism of injury and date of injury, presentation, and surgical repair were collected. This process was repeated for the same dates in the previous 5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…The widespread use of online ophthalmic consultation services during the outbreak further confirmed this view ( 28 ). In addition, there was a trend of delay in emergency department visits for ocular trauma, and Stedman et al ( 36 ) revealed that the delay between onset and visit increased from 0.33 days to 1.1 days before and after COVID-19, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The widespread use of online ophthalmic consultation services during the outbreak further confirmed this view ( 28 ). In addition, there was a trend of delay in emergency department visits for ocular trauma, and Stedman et al ( 36 ) revealed that the delay between onset and visit increased from 0.33 days to 1.1 days before and after COVID-19, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective cohort analysis in the United Kingdom noted that the number of serious ocular traumas, including rupture, lid lacerations, and IOFB, was three times the average over the past 5 years, with a 400% increase in hospital admissions due to DIY activities after the outbreak ( 36 ). Wu et al ( 35 ) also reported a nearly 30% increase in the proportion of serious ocular trauma caused by home improvement during the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Injuries sustained due to falls and home improvement projects were a major cause for this increase. 19 …”
Section: Discussionmentioning
confidence: 99%
“…The reduction in patient numbers varied depending on the ocular injury, as is in line with previous reports. [14][15][16] This could be explained by the change of the injury setting, i.e., the types and frequency of injuries typically occurring in workplaces, schools, and during social activities may differ to the those occurring at home during the lockdown. 15,16 During the lockdown, there was a considerable decrease in the percentage of patients complaining of non-specific visual symptoms without a related pathology, demonstrating that many patients that usually present to the OES, probably do not need emergency care.…”
Section: Discussionmentioning
confidence: 99%